Identification, Characterization, and Expression Analysis of Cell Wall Related Genes in Sorghum bicolor (L.) Moench, a Food, Fodder, and Biofuel Crop - Rai, Krishan M.; Thu, Sandi W.; Balasubramanian, Vimal K.; Cobos, Christopher J.; Disasa, Tesfaye; Mendu, Venugopal (Frontiers in Plant Science, 2016)
Biomass based alternative fuels offer a solution to the world’s ever-increasing energy demand. With the ability to produce high biomass in marginal lands with low inputs, sorghum has a great potential to meet second-generation biofuel needs. Despite the sorghum crop importance in biofuel and fodder industry, there is no comprehensive information available on the cell wall related genes and gene families (biosynthetic and modification). It is important to identify the cell wall related genes to understand the cell wall biosynthetic process as well as to facilitate biomass manipulation. Genome-wide analysis using gene family specific Hidden Markov Model of conserved domains identified 520 genes distributed among 20 gene families related to biosynthesis/modification of various cell wall polymers such as cellulose, hemicellulose, pectin and lignin. Chromosomal localization analysis of these genes revealed that about 65% of cell wall related genes were confined to four chromosomes (Chr. 1-4). Further, 53 tandem duplication events involving 146 genes were identified in these gene families which could be associated with expansion of genes within families in sorghum. Additionally, we also identified 137 Simple Sequence Repeats related to 112 genes and target sites for 10 miRNAs in some important families such as cellulose synthase, cellulose synthase-like and laccases, etc. To gain further insight into potential functional roles, expression analysis of these gene families was performed using publicly available data sets in various tissues and under abiotic stress conditions. Expression analysis showed tissue specificity as well as differential expression under abiotic stress conditions. Overall, our study provides a comprehensive information on cell wall related genes families in sorghum which offers a valuable resource to develop strategies for altering biomass composition by plant breeding and genetic engineering approaches.